(untitled) (ModaPalavra e-periódico, 2024)
Sport and society have developed increasingly complex interactions in the competitive globalized world. The aim of this article is to analyze the discursive construction around the uniforms used by Brazilian women’s volleyball teams, based on the perception of athletes who competed in the Olympic Games for the national team, between the years 1980 and 2012. The methodology used correlates notes from the literature with testimonials from athletes collected through interviews. It is verified that there is a gradual concern with the design of uniforms, which pervades material, symbolic, and mediatic aspects. It is concluded that the design of uniforms for women has become a central theme for the discussion on gender in sports.